The Approximate Function of Speech in the Regulation of the Joint Activity of Preschool Children - Smirnova, Y.K. (Psihologo-pedagogičeskie issledovaniâ, 2019)
The article reveals the provisions that speech is used by preschool children in joint activities as a means of orientation in the process of developing an action plan. The goal was to identify the role of speech in the implementation of the exploratory search activity of the members of the group in the course of joint activities, as well as to develop control over the actions of preschool children. The study involved 147 preschool children, who were organized during the experiment in subgroups to jointly solve problematic situations. To illustrate the approximate role of speech in regulating the joint activity of preschoolers, Structural Equations (SEM) modeling was applied. A model is constructed that reflects the combined functional links of the regulation of the joint activity of preschool children. It is proved that in the structure of the regulation of joint activity speech provides an afferent synthesis of the conditions of activity, facilitates the analysis of internal and external conditions of joint activity, the development of a program of conscientious activity. It is shown that for preschool children, speech orientation tools are used as a mechanism for controlling and correcting behavior. В статье раскрываются положения о том, что речь используется дошкольниками в совместной деятельности как средство ориентировки в процессе выработки плана действия. Целью стало отображение роли речевых средств ориентировки в становлении контроля поведения дошкольников в процессе взаимодействии со сверстниками. В исследовании приняли участие 147 детей дошкольного возраста, которые были организованны в ходе эксперимента в подгруппы для совместного решения проблемных ситуаций. Для отображения ориентировочной роли речи в регулировании совместной деятельности дошкольников было применено моделирование структурными уравнениями (SEM). Построена модель, отображающая объединенные функциональные звенья регуляции совместной деятельности дошкольников. В структуре регуляции совместной деятельности речь обеспечивает афферентный синтез условий деятельности, способствует анализу внутренних и внешних условий совместной деятельности, выработке программы совестной деятельности. Показано, что у дошкольников речевые средства ориентировки используется как механизм контроля и коррекции поведения.